Pengembangan Aplikasi Penentuan Media Promosi Pelaku UMKM Berbasis Website - Subiyantoro, Edi; Rofiqul Muslikh, Ahmad; Yulian Pamuji, Fandi; Wunu, Maria Elfrida (Jurnal Teknologi dan Manajemen Informatika, 2023)
Today, with the presence of digital technology, UMKM actors in Indonesia have numerous opportunities to create job opportunities and expand their businesses to the global market. However, not all UMKM actors in Indonesia have sufficient understanding and knowledge of the current digital technology being used. This research aims to design a system that can assist UMKM actors to increasing their product sales volume by developing an effective and efficient web-based application for selecting promotional media for UMKM. The testing of the UMKM AHP Application system, based on a black box method, is conducted to identify any potential issues in the application and ensure its readiness for publication. This testing covers various pages such as Criteria page, Alternative page, AHP Preference Value page, Criteria Analysis page, Alternative Analysis page, Ranking Report page, Report page, Profile page, and Logout page.